2004
DOI: 10.1007/s00415-004-0418-z
|View full text |Cite
|
Sign up to set email alerts
|

Does serum prolactin indicate the presence of seizure in the emergency department patient?

Abstract: The measurement of serum prolactin is helpful as a confirmatory test, but not as screening test in the emergency department setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Vukmir in his study concluded that an elevated serum PL is a reliable confi rmatory test, for epilepsy compared to febrile seizure 14 .…”
Section: Discussionmentioning
confidence: 98%
“…Vukmir in his study concluded that an elevated serum PL is a reliable confi rmatory test, for epilepsy compared to febrile seizure 14 .…”
Section: Discussionmentioning
confidence: 98%
“…6 Prolactin can also be raised after a generalized tonic-clonic seizure and after a nonepileptic seizure as well as after a syncope, indicating that increased prolactin levels cannot be used to differentiate between seizures, syncope, and GHB intoxication. 7,8 Patients who suffered from a generalized tonic-clonic insult have a marked elevation of lactate and often suffer from lactate acidosis. 9 The treatment of GHB intoxications is supportive because no antidote is available.…”
Section: Discussionmentioning
confidence: 99%
“…Además, se debe insistir en la necesidad de incrementar el porcentaje de determinación de tóxicos en una sociedad donde el consumo de estas sustancias cada vez es más frecuente. Contrariamente, los niveles de prolactina sérica no suelen estar disponibles en los servicios de urgencias durante las 24 horas por lo que su utilidad se ha mostrado reducida (13).…”
Section: Discussionunclassified